A reproducible endothelial-state contrast with limited bulk prognostic robustness in hepatocellular carcinoma - Si-yuan Tan; Lan-hui Qin; Wenqing Liang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Yu Zhang; Liling Long (Functional & Integrative Genomics, 2026)

Engineered aptamer-confined hydrogel for label-free detection of heavy-metal ions with enhanced interference tolerance - Long Bai; Xiuxiu Wu; Lei Huang; Haohao Chen; Jinsong Yu; Ziqing Ye; Min Yuan; Hui Cao; Liling Hao; Fengqin Yin; Tai Ye; Fei Xu (Food Chemistry, 2026)

A high-performance direct biomass fuel cell utilizing red bean shell as fuel - Guangkai Lu; Boyuan Liu; Liling Long; Yundong Qian; Xiaoyuan Zeng; Senran Hao; Weizi Cai; Jie Xiao (Fuel, 2026)

TMC6 Protects Against Ischemic Neuronal Injury by Activating Rap1/Rac1 Signaling to Restore Mitochondrial Dynamics and Mitophagy - Xuemei Quan; Huo Liang; Haiyin Long; Xiawei Wang; Liling Feng; Xia Zhou; Yuan Chen; Yanhua Li; Xiaofeng Li (Molecular Neurobiology, 2026)

Ontogenetic niche segregation and its implications for mercury levels in Japanese anchovy from the high seas of the northwestern Pacific Ocean as revealed by fatty acid analysis - Long Chen; Zhenfang Zhao; Guanyu Hu; Liling Zhang; Bilin Liu; Xinjun Chen (Journal of Fish Biology, 2025)
Japanese anchovy ( Engraulis japonicus ) is a small pelagic fish that is frequently targeted by commercial fisheries. Japanese anchovy plays a crucial role as a vital link between primary and higher‐order consumers. The elemental mercury in Japanese anchovy muscles easily bioaccumulates and is transmitted to top predators. We investigated the variation in the diets and mercury accumulation of Japanese anchovy in the high seas of the northwestern Pacific Ocean. We measured the amounts of mercury and fatty acids in the muscles of 149 Japanese anchovy specimens that were obtained from the open seas of the northwestern Pacific Ocean (39°2′ N ~ 42°30′ N, 154°02′ E ~ 161°29′ E) between June and July 2021. The results revealed that the monounsaturated fatty acid (MUFA) and polyunsaturated fatty acid (PUFA) contents significantly decreased and then increased with the growth of Japanese anchovy ( p

Study on the effect of heat treatment process on the quality characteristics of soybean-Citri Reticulatae Pericarpium (CRP) based yogurt and related mechanisms - Juan Zhang; Yue Long; Yanpeng Zhang; Liling Lu; Chenxu Liu; Wei Xu; Zhixiong Hu; Chun Hu (Food Hydrocolloids, 2025)

Fluorescent nanozyme for the dual-mode detection of tetracycline: Aggregation-induced luminescence and boosting peroxidase-like activity - Tai Ye; Long Bai; Jinsong Yu; Weiyan Shi; Min Yuan; Juncheng Wang; Hui Cao; Liling Hao; Xiuxiu Wu; Fengqin Yin; Fei Xu (Food Control, 2025)

Spatial single-cell maps reveal ST6GAL1 promoting ovarian cancer metastasis - Lan-hui Qin; Zijian Jiang; Chongze Yang; Rui Song; Pei-yin Chen; Weihui Xu; Guanzhen Zeng; Jin-yuan Liao; Liling Long (Glycoconjugate Journal, 2025)

Bi2O2Se nanosheets coated with rosmarinic acid for colon-targeted treatment of inflammatory bowel disease - Jiahu Yao; Yang Yang; Hu Zhao; Chuanming Wang; Liang Jin; Tengyun Long; Wei Huang; Xiang Zhan; Xin Li; Xin Chen; Jinhu Xie; Bin Wu; et al. (Chemical Engineering Journal, 2025)

Effects of diet and habitat on Hg levels in Japanese anchovy in the high seas of the northwestern Pacific Ocean - Long Chen; Guanyu Hu; Zhenfang Zhao; Bilin Liu; Xinjun Chen; Liling Zhang (Marine Pollution Bulletin, 2024)

Insight into selenium biofortification and the selenite metabolic mechanism of Monascus ruber M7 - Lisha Zhu; Pengcheng Long; Man Hu; Liling Wang; Yanchun Shao; Shuiyuan Cheng; Xingxing Dong; Yi He (Food Chemistry, 2024)

Glutamicibacter nicotianae AT6: A new strain for the efficient biodegradation of tilmicosin - Huijuan Li; Hao Zhou; Liling Fan; Long Meng; Yanyun Zhao; Lanmei Zhao; Bo Wang (Journal of Environmental Sciences, 2024)

Liangyi Gao extends lifespan and exerts an antiaging effect in Caenorhabditis elegans by modulating DAF-16/FOXO - Liling Zeng; Chen Sun; Zhong Pei; Tianchan Yun; Shaoyi Fan; Simei Long; Tengteng Wu; Ziwen Chen; Zhimin Yang; Fuping Xu (Biogerontology, 2019)